China Energy Policy: Evidence of China-Russia Cooperation - Trubnikov, Vladislav; Richter, Ulf Henning (International Journal of Energy Economics and Policy, 2019)
This paper proposed the importance of a social synergy approach in China-Russia cooperation. Traditional energy transportation activities are viewed as an element of the environmental concern in both countries. Liquefied natural gas (LNG) transportation might be a better solution as an alternative to other options. LNG market is becoming more and more developed and Russia is actively looking to incorporate this energy strategy. The shale gas revolution in the USA has led to environmental degradation in the affected areas. Extraction of this type requires a sophisticated and expensive technology, because of which many emerging countries don`t have it. The results show that China is interested in the economic benefits of such investment activities and does not intervene in the political sphere of these countries. Keywords: Alternative Energy Sources, Energy Policy, Resource Saving, Energy Efficient Development, Energy Indicators. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8540